Legal Protection for Online Transaction Users: A Review of The Constitution No. 8 of 1999 Regarding Consumer Protection - Wahyuni Safitri; Wafda Vivid Izziyana (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2020)
Legal protection for consumers in an electronic commerce transaction in Indonesia is crucial for the development of the society’s economy. The aim of this research is to know how is the legal protection for online transaction users is in Indonesia. The method of study is the juridicial-normative method. The data collection is done through literature study. The research results show that the legal protection in the Electronic Transaction Agreement in Indonesia is regulated in Articles 47 and 48 of the Governmental Decree, No. 82 of 2012 regarding the Establishment of the Electronic System and Transaction. Legal protection for the society is written in Article 46 of the Constitution No. 11 of 2008 regarding Electronic Information and Transaction and Article 62 of the Constitution No. 8 of 1999 regarding Consumer Protection. Legal protection towards consumers in electronic transaction in Indonesia is regulated strictly both in the aspects of criminal and civil laws. Keywords: law; online transaction; consumer protection.